Local issues of virus infections in various food and horticultural crops as a biology learning resource to support the SDGs - Sri Handayani; S. Suranto; Umi Fatmawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Local problems in the surrounding environment can be developed in school learning according to independent curriculum policies so that students are responsive and can play an active role in solving problems, such as those related to viruses and their role. This study aims to determine the symptoms of viral infections in various food and horticultural crops through direct understanding and their potential as a source of biology learning. This study uses qualitative and quantitative approaches. Data collection methods through unstructured interviews, observations, and questionnaires. The research instrument is in the form of a questionnaire sheet of learning resource potential. Data analysis techniques are carried out descriptively and percentage calculations. This study showed in the Kebakkramat Karanganyar area, in addition to rice plants, other plants were infected with the virus. The virus infection in these plants showed different symptoms. The potential for viral infection in food and horticultural crops as a learning resource showed an average of 86.11%, which means it is very good. Therefore, the local issue of viral infections in food and horticultural crops is very good as a learning resource for biology for class X students on the material on viruses and their role in supporting SDG4. This learning resource can be developed as a learning medium integrated with appropriate learning methods.